Numerical investigation of heat transfer characteristics of moderator assembly employed in a low-enriched uranium nuclear thermal propulsion reactor - Li, Wei; Guan, Chaoran; Song, Houde; Chai, Xiang; Liu, Xiaojing (Frontiers in Energy Research, 2022)
The design of a nuclear thermal propulsion (NTP) reactor based on low-enriched uranium (LEU) requires additional moderator elements in the core to physically meet the critical requirements. This design softens the core energy spectrum and can provide more thermal neutrons for the fission reaction, but the heat transfer characteristics between the fuel and moderator assembly are more complex. Aiming at the typical LEU unit design, the heat transfer mathematical model is established using the principle of heat flow diversion and superposition. The model adopts the heat transfer relationship based on STAR-CCM+ simulation rather than the empirical expression used in the past literature to improve the applicability of the model. The heat transfer coefficients in the proposed model are evaluated under different Reynolds numbers and thermal power. The deviations between the proposed model and CFD simulation are analyzed. The results show that the calculation of the heat transfer coefficient between the proposed model and the CFD simulation maintains a good consistency, most of which are within 10%. It may provide a reliable and conservative temperature estimation model for future LEU core design.